Kidney disease, Ceruloplasmin & Hypertension (Journal of the College of Basic Education, 2023)
The aim of the present study was to estimate the relationship between the urea , creatinine , ceruloplasmin and blood pressure in patient with nephropathy this study include 75 patients with nephropathy collected from Baghdad hospital (30 females and 45males ) and 32 sample collected from healthy subject as control group with age range of (40-80 years ); patient were divided into three age group (40-50 ) (51-60 ) and >60 years. urea , creatinine , ceruloplasmin , blood pressure was determined for both patient and control subject. Results showed that all patient had increased level of urea, creatinin, ceruloplasmin and blood pressure which were statistically significant when compared with control group P< 0.01 the mean urea level in patients (46.5mg/dL) compare with control group (25.5mg/dL) P<0.01 creatinine level in patient were (1.9mg/dL) compare with control group (0.8mg /dL) P<0.01 cerulopasmin .level in patient were (74.8mg/dL ) compare with control group (57.2 mg/dL) P<0.01 and blood pressure for patients with nephropathy were (16.1/10.1 ) mm Hg compare with control group (12.5/8.5) mmHg P<0.01